PROYECT METHOD AND ITS EFFECT ON LEARNING COURSE IN STATISTICS GENERAL UNDERGRADUATE STUDENTS UNIVERSITY - Vega Durand, Elba (2012)
The present research project entitled the method and its effect on learning of general statistics course for undergraduates César Vallejo University-Lima Subsidiaria, 2010-II, the aim of determining the effect of the project-based method in learning general statistics course for undergraduate students. Research regarding its methodology is descriptive-explanatory method and ex post facto correlational design. For data collection a questionnaire applies to students who collects feedback on the study variables. In relation to the sample, this is a statistically representative sample consisted of 100 students of vocational schools Environmental Engineering, Accounting and Psychology. For data processing software was used SPSS version 19. Among the most important conclusions we can say that the implementation of the project-based method has positive effect on learning of descriptive statistics, probability and statistical inference, thereby accepting the general hypothesis, "The application of project-based method has positive effect learning in general statistics course for undergraduates".